Academic Procrastination Among Working Undergraduate Students: A Descriptive Study at Universitas X - Shafia Salsabila; Sandra Adetya; Mic Finanto Ario Bangun (Socrates: Journal of Education, Philosophy and Psychology, 2026)
Academic procrastination has become one of the most common academic problems experienced by university students, particularly those who simultaneously pursue higher education and employment. Balancing academic responsibilities with occupational demands may create challenges that increase the tendency to delay academic tasks. This study aimed to describe the level of academic procrastination among working undergraduate students at Universitas X. This study employed a quantitative descriptive research design involving 167 working undergraduate students selected using proportional stratified random sampling. Data were collected using the Indonesian version of the Multidimensional Academic Procrastination Scale (MAPS-15), which demonstrated acceptable validity and reliability before the main data collection. Descriptive statistical analysis was conducted using JASP version 0.19.7.1 to calculate the mean, standard deviation, frequencies, percentages, and category distribution of academic procrastination. The findings revealed that 53.9% of respondents were categorized as having a high level of academic procrastination, 34.1% were categorized as having a low level, and 12.0% were categorized as having a moderate level. These findings indicate that academic procrastination remains prevalent among working undergraduate students at Universitas X. The study provides a descriptive overview of academic procrastination among working students and contributes empirical evidence that may assist higher education institutions in understanding the academic characteristics of students who undertake dual roles as learners and employees.